SOSIALISASI PENGELOLAAN LIMBAH PERIKANAN UNTUK MENINGKATKAN KESADARAN LINGKUNGAN DI KALANGAN NELAYAN DI TANJUNG LUAR, LOMBOK TIMUR - Fitriani, Laily; Sumsanto, Muhammad; Dermawan, Awan; Dwiyanti, Septiana; Asri, Yuliana (Jurnal Pengabdian Perikanan Indonesia, 2024)
Fishery waste management activities are an important issue in maintaining the sustainability of the coastal environment. In the Tanjung Luar area, East Lombok, dense fishing activities have the potential to produce large amounts of organic and inorganic waste. This community service activity aims to increase fishermen's awareness of the impacts of fishery waste and the importance of sustainable management through socialization activities. The methods used are counseling and participatory group discussions with local fishermen. The results of the activity showed an increase in participants' knowledge about the types of waste and how to handle it. This activity is expected to be the first step towards more environmentally friendly fisheries practices in coastal areas.